Materiality of Non-financial Sustainability Disclosures: Implications for the Business Enterprises in Bangladesh - Mamun, Ashraf Al (Asian Business Review, 2018)
In disclosing non-financial sustainability information, materiality of information may be a crucial factor to be considered, which is a new concept in sustainability reporting area. It outlines the significance of materiality assessments while realizing the content of sustainability reports with the identification of those economic, environmental and social issues that matter most to a company and its stakeholders. In this regard, GRI guidelines have been considered worldwide as a tool of disclosing non-financial material sustainability information by the business enterprises. The paper reviews relevant literature as methodology and discusses the conceptual framework of non-financial disclosure of material sustainability information and its implications for the business enterprises in Bangladesh. The paper finds that non-financial disclosure of material sustainability information is at a very nascent stage in Bangladesh and there is ample scope to disclosure of non-financial material sustainability information for the business enterprises in Bangladesh.
Keywords: Materiality; non-financial disclosure; material sustainability information; sustainability reporting; GRI guidelines